Accessibility and transport appraisal: Approaches and limitations - Karst Guers (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2020)
This paper describes the different approaches to measuring accessibility benefits and the limitations of their application in practice. It argues that a broader perspective on accessibility measurement and valuation beyond the current focus on time savings will improve transport appraisal. Notably the better utilisation of land use and transport interaction models will benefit transport investment appraisal.
Keywords: 330